Site index models for Calabrian pine in the central Mediterranean region of Turkey - Kahriman, Aydin; Sönmez, Turan; von Gadow, Klaus (Taylor & Francis Inc, 2018)
Stem analysis data of 432 trees were obtained from even-aged, pure natural stands of Calabrian pine in the central Mediterranean Region of Turkey. Eight dynamic site equations derived with the Generalized Algebraic Difference Approach (GADA) were compared, based on autoregressive analysis and a thorough evaluation of the goodness of fit. We used generalized nonlinear least squares methods for model fitting. The adjusted coefficients of determination (0.9825-0.9842), root-mean-square errors (0.8004-0.8435 m), and Akaike's information criterion differences (0-145) indicated a good fit of the eight site index equations. The Hossfeld equation (M3) provided the best result. The Durbin-Watson test statistic did not reveal an autocorrelation issue while the Hossfeld equation provided a satisfactory solution to the serial correlation problem in stem analysis data as time series using autoregressive modeling. This study presents new site index models for Calabrian pine forests in the central Mediterranean region of Turkey where it is the most important commercial tree species. The site index equation, based on the Hossfeld model is recommended for height growth prediction and site classification of Calabrian pine stands in the central Mediterranean region of Turkey, providing a new basis for growth prediction and yield estimation in these important forest ecosystems.
Keywords: Site index models; generalized algebraic difference approach; autoregressive modeling approach; calabrian pine; Hossfeld model